Impact of Parental Involvement in Training Social Skills to Children with Multiple Disabilities - Kuppan, Dhanavendan Kunju; Mathaiyan, Vakkil (International Journal of Psychosocial Rehabilitation, 2020)
Multiple Disabilities means as an individual having two or more than two types of disabilities in which required more attention and support in education programming. It is also called double disabilities or complex disability in various occasions. The purpose of the study is to investigate the social skill deficits in children with multiple disabilities and their effect of parental involvement in training social skills. Sixty parents and their children selected for this study with purposive sampling technique. The investigator used adapted functional assessment checklist to measure the independencies in social skills of children with multiple disabilities and parental involvement questionnaire to measure their involvement in training social skills whether no, low, moderate and high. The results found that there is a significant difference in social skills and their parental involvement in training. Parental involvement is extremely important to the ultimate success of their child’s program.